Multiphase Calcite Cementation and Fluids Evolution of a Deeply Buried Carbonate Reservoir in the Upper Ordovician Lianglitag Formation, Tahe Oilfield, Tarim Basin, NW China - Jiaqing Liu; Zhong Li; Lijuan Cheng; Jiawei Li (Geofluids)
Oil and gas have been found in the Upper Ordovician Lianglitag Formation carbonates in the Tahe Oilfield, Tarim Basin, NW China. This study documents the origin of diagenetic fluids by using a combination of petrology, SIMS, fluid inclusion, and radiogenic isotope analysis. Six stages of calcite cements were revealed. C1-C2 formed in marine to early burial environments. C3 has relatively low δ18OVPDB values (−8.45‰ to −6.50‰) and likely has a meteoric origin. Meteoric water probably fluxed into aquifers during the Early Paleozoic and Late Paleozoic uplift. C4 has δ18OVPDB values typically 3‰ higher than those of C3, and probably formed during shallow burial. C5 displays relatively negative δ18OVPDB values (−8.26‰ to −5.12‰), and the moderate-to-high fluid-inclusion temperatures imply that it precipitated in burial environments. C6 shows homogenization temperatures (up to 200°C) higher than the maximum burial and much lower salinities (<10.61 wt% NaCl), which may suggest that the fluid was deeply recycled meteoric water. The average 87Sr/86Sr ratios of fracture- and vug-filling calcite cements are much higher, indicative of incorporation of radiogenic Sr. Caves and fractures constitute the dominant reservoir spaces. A corresponding diagenesis-related reservoir evolution model was established that favors exploration and prediction.